Regulation of NAD(P)H quinone oxoreductase 1 (NQO1) in SHSY-5Y neuroblastoma cells by chemopreventive agents - Gwarzo, Muhammad Yalwa (Free Radicals and Antioxidants)
Introduction: High level of polyunsaturated fatty acids of lipid bilayer membrane coupled with increased oxygen consumption exposed brain cells to oxidative stress. Oxidative stress has been implicated as the etiological factor of many neurodegenerative diseases. Chemopreventive agents both synthetic and natural have the potential of inducing endogenous antioxidants with the capability of attenuating oxidant induced damage. This wok examined the ability of tert-butylated hydroxyl quinone (tBHQ), ethoxyquin, coumarin and selenium to induce NAD(P)H quinine oxoreductase 1 (NQO1) in neuroblastoma cell line. Method: SHSY-5SY neuroblastoma cells were culture in medium containing 100 mM of the individual chemopreventive agents or in combination with 50 nM sodium selenite. The cells were harvested after 24 h exposure with the chemopreventive agents. Protein levels were determined by immunoblotting, while enzyme assay was done using dichloro-phenol-indo-phenol as a substrate in the presence of NADH and FAD to determine reductase activity, while dicumarol was used as an inhibitor of NQO1. Results: Coumarin, ethoxyquin and tBHQ-induced NQO1 marginally (1.2e1.5-fold). Treatment of cells with selenium as sodium selenite together with tBHQ-induced NQO1 by about 3-fold compared with control. The enzyme activity was significantly increased by all chemopreventive agents (p < 0.05). Conclusion: Inducers of endogenous antioxidants that can pass bloodebrain barrier provide hope of delaying and attenuating neurodegenerative diseases associated with either increased free radical production or genetic predisposition.
Keywords: Antioxidants; SHSY-5SY; NQO1; Selenium; tert-butylated hydroxyl quinone